Micromorphology and ultrastructure of anthers and pollen grains in ten elite genotypes of Theobroma cacao (Malvaceae) - Rincón Barón, Edgar Javier; Zarate, Diego Alejandro; Castañeda, Genaro Andrés Agudelo; Cuarán, Viviana Lucia; Passarelli, Lilian M. (Revista de Biología Tropical, 2021)
Introduction: Despite the fact that T. cacao is an important species worldwide for cocoa production, little is known about the micromorphology and structure of anthers and pollen grains. Objectives: To describe and analyze the structure and micromorphology of the anthers and pollen grains of 10 elite genotypes of this important tropical species. Methods: More than 30 anthers of flowers in anthesis were taken of the 10 elite genotypes of T. cacao from the ex situ germplasm bank of the Suiza-Agrosavia Research Center (Rionegro, Santander-Colombia). The anthers with the pollen grains were fixated and processed according to the standard protocols for embedding and sectioning in paraffin. Sections obtained (3 μm thick) were stained with Safranin-Alcian blue to discriminate structures with primary and secondary walls and total polyphenols. Additionally, the samples were also stained with the PAS-Amidoblack technique was used to differentiate between structural and reserve polysaccharides as well as proteins. Toluidine blue staining was used for the determination of sporopollenin and polyphenols and finally Alcian blue-PAS-Hematoxylin staining was applied for additional descriptions. Observations were made using photonic microscopy and epifluorescence microscopy. For observation with scanning electron microscopy (SEM) the anthers with the pollen grains were fixed and dehydrated in 2.2 Dimethoxypropane, then desiccated to critical point and finally coated with gold. Results: the anthers are dithecal and supported by a long filament made up of an epidermal stratum, parenchymal tissue, and a vascular bundle. The dehiscence occurs longitudinally through the stomium. The anther wall is made up of a monostratified epidermal layer, followed by a layer of endothecial cells with lignified fibrillar thickenings, cellular remnants of tapetum and abundant orbicules can be seen covering the cavity of the microsporangia. The epidermal and parenchymal tissues of the anthers are abundant in polyphenols. Orbicules are generally spherical, psilated, and these exhibit the same staining and fluorescence reactions as exine from pollen grains. The pollen grains are monades, isopolar, small (16-19 µm) with circular amb, spheroidal, tricolpate with medium or short colpi (5-10 µm) with sculptured membrane, semitectate, reticulated, heterobrochate, sculptured or non- sculptured walls, with microgranules of different size or scabrate. The statistical analyzes showed that there are significant differences in the size of the pollen grains (P ˂ 0.05). It is observed that the smallest pollen grains are those of the TCS 19 genotype (16.890 µm) and are different from the other genotypes, and among these there are no significant differences. Only two genotypes (SCC 19 and SCA 6) Observable pollenkitt and only one has perforated walls (SCA 6). Conclusions: The structure and micromorphology of the anthers of T. cacao are similar to those described for other Malvaceae. Likewise, the pollen grains showed variations in size, ornamentation of the sporoderm and the lumen of the reticulum and the presence of pollenkitt. However, no relationship was observed between the micromorphological characters analyzed in the pollen grains and the pollen compatibility models reported for these genotypes.